2019
DOI: 10.2478/jec-2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Financial Performance Transparency of Public Benefit Organisations

Abstract: Research purpose. The aim of the research is to assess the transparency of financial performance of public benefit organisations (PBOs). Methodology. To achieve the aim and to accomplish the tasks set, general-scientific methods were used: the monographic method, the method of document analysis and the graphical method. A statistical analysis method – descriptive statistics – and a sociological research method – surveying – were used as well. Findings. Since 1 October 2014 when the Public Benefit Organisation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Within this catalogue should also be indicated, in reference only to organizations with the status of public benefit organizations, the Head of the Public Benefit Committee, who took over the supervisory powers of the minister competent for social security rights in the correct use with the law, just like it is in the majority of other European countries 65 is supervised through two major information sources -annual financial reports containing financial information and annual performance reports (previous year performance reports and future activity plans), that contain qualitative or descriptive information 66 . The Public Benefit Commission in is a collegial institution, which equal numbers shall include officials, as well as representatives of associations and foundations 67 .…”
Section: Entities Authorized In the Field Of Supervision And Control Over Non-governmental Organizationsmentioning
confidence: 99%
“…Within this catalogue should also be indicated, in reference only to organizations with the status of public benefit organizations, the Head of the Public Benefit Committee, who took over the supervisory powers of the minister competent for social security rights in the correct use with the law, just like it is in the majority of other European countries 65 is supervised through two major information sources -annual financial reports containing financial information and annual performance reports (previous year performance reports and future activity plans), that contain qualitative or descriptive information 66 . The Public Benefit Commission in is a collegial institution, which equal numbers shall include officials, as well as representatives of associations and foundations 67 .…”
Section: Entities Authorized In the Field Of Supervision And Control Over Non-governmental Organizationsmentioning
confidence: 99%
“…Online dissemination of accountability related information can provide opportunities for mutual information exchange between stakeholders, e.g., via a typical tool like a public blog on the NGO's website [18]. It has been previously shown that the public is interested in understanding the impact of the nonprofit sector; for instance, Voitkane & Jakusonoka [19] analyzed the voluntary disclosure of financial information on the websites of public benefit organizations in Latvia. Despite the fact that 47% of the respondents in their survey showed interest in retrieving online information through an organization's website, only 22% of the organizations share financial data [19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that the public is interested in understanding the impact of the nonprofit sector; for instance, Voitkane & Jakusonoka [19] analyzed the voluntary disclosure of financial information on the websites of public benefit organizations in Latvia. Despite the fact that 47% of the respondents in their survey showed interest in retrieving online information through an organization's website, only 22% of the organizations share financial data [19]. Realizing the importance of the internet as an online tool for dissemination of information, researchers have designed indices to monitor the quality of information shared online by the NGO.…”
Section: Introductionmentioning
confidence: 99%